2018
DOI: 10.1007/s00702-018-1878-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral mechanisms underlying the maternal disruptive effect of serotonin 5-HT2A receptor activation in Sprague–Dawley rats

Abstract: Recent evidence indicates that acute activation of 5-HT receptors causes a disruption of maternal behavior in rats. However, the behavioral mechanisms underlying such a disruption are not known. We addressed this issue using two behavioral approaches targeting the maternal motivational and emotional processing systems. First, we used the pup-separation technique to increase maternal motivation to see whether pup separation is capable of reducing the maternal disruptive effect of TCB-2 (a high-affinity 5-HT ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…To test this, postpartum females were treated subcutaneously with the 5-HT2A agonist TCB-2 or the 5HT2C agonist MK 212, or vehicle, and tested after either a 4-h pup-separation or no-pup-separation [144; 145]. Although the 4-h pup separation before maternal behavior tests increased maternal performance (e.g., increased time spent nursing and licking pups), it did not reduce the 5-HT2A agonist-induced maternal disruption [144]. In contrast, pup separation significantly attenuated the 5-HT2C agonist-induced decrease in retrieval [145].…”
Section: Specific Effects Of 5-ht2a and 5-ht2c Receptors On Maternal mentioning
confidence: 99%
See 2 more Smart Citations
“…To test this, postpartum females were treated subcutaneously with the 5-HT2A agonist TCB-2 or the 5HT2C agonist MK 212, or vehicle, and tested after either a 4-h pup-separation or no-pup-separation [144; 145]. Although the 4-h pup separation before maternal behavior tests increased maternal performance (e.g., increased time spent nursing and licking pups), it did not reduce the 5-HT2A agonist-induced maternal disruption [144]. In contrast, pup separation significantly attenuated the 5-HT2C agonist-induced decrease in retrieval [145].…”
Section: Specific Effects Of 5-ht2a and 5-ht2c Receptors On Maternal mentioning
confidence: 99%
“…To further examine this issue, Wu and colleagues (2018) tested TCB-2-treated dams in a pup-male preference test to determine whether 5-HT2A receptors activity reduced pup preference when dams were faced with two socially rewarding stimuli [160; 161]. Activating the 5-HT2A receptor increased pup preference in this test [144] such that dams treated with the 5-HT2A agonist, TCB-2, spent more time exploring the pups than the male, and showed a greater percentage of exploration time with pups compared to controls. This finding, together with the results from the maternal motivation study, further suggest that the 5-HT2A agonist TCB-2 disrupts maternal behavior by suppressing maternal motivation.…”
Section: Specific Effects Of 5-ht2a and 5-ht2c Receptors On Maternal mentioning
confidence: 99%
See 1 more Smart Citation
“…If it does, TCB-2-treated dams should have performed better under the pup separation condition than under the no-separation condition. The second piece of evidence comes from a pup vs. male preference test (Wu et al, 2018). In this study, we found that TCB-2-treated dams increased time spent with pups and decreased time with male.…”
Section: Introductionmentioning
confidence: 59%
“…The 5HT has multiple effects on maternal behaviors, depending on which receptor systems and brain regions are affected. 115 The 5HT brain levels in rats are associated with maternal aggression and maternal behavior; different 5HT receptor agonists increase maternal aggression and disrupt expression of many maternal behaviors, without affecting maternal motivation, affect, or stimulus salience per se, 149 although some 5HT agonists seem to disrupt aspects of maternal startle and attention. [150][151][152] In primates, 5HT is implicated in anxiety arousal of mothers 153 and lower CSF 5HIAA levels associate with more restrictive and rejecting maternal behaviours.…”
Section: Dopaminementioning
confidence: 99%